Positive and negative ions of the amino acid histidine formed in low-energy electron collisions - Meißner, Rebecca (2020)
Agence Nationale de la Recherche, Grant/Award Numbers: ANR-10-LABX-0066 and ANR-11-IDEX-0007; Austrian Science Fund, Grant/Award Number: P30332; Ministerio da Ciencia, Tecnologia e Ensino Superior, Grant/Award Number: P7440-035-011; University of Innsbruck; Investissements d'Avenir; LABEX Lyon Institute of Origins; Institut de Physique Nucleaire de Lyon; Radiation Biology and Biophysics Doctoral Training Programme, Grant/Award Number: PD/00193/2012; Portuguese National Funding Agency FCT-MCTES, Grant/Award Numbers: PTDC/FIS-AQM/31281/2017, UID/FIS/00068/2019 and PD/BD/114452/2016; FWF, Vienna, Grant/Award Number: P30332